The fortune of war eaudiobook - O'Brian, Patrick (Aubrey & Maturin, 2012)
En route home, Aubrey and Maturin find themselves in deep trouble when their ship engages the U.S.S. Constitution in battle-and loses. Aubrey, now a POW in Boston, waits for word of a prisoner exchange, while Maturin renews a most cherished friendship.